2016
DOI: 10.1007/978-3-319-42291-6_83
|View full text |Cite
|
Sign up to set email alerts
|

A Framework on a Computer Assisted and Systematic Methodology for Detection of Chronic Lower Back Pain Using Artificial Intelligence and Computer Graphics Technologies

Abstract: Abstract. Back pain is one of the major musculoskeletal pain problems that can affect many people and is considered as one of the main causes of disability all over the world. Lower back pain, which is the most common type of back pain, is estimated to affect at least 60% to 80% of the adult population in the United Kingdom at some time in their lives. Some of those patients develop a more serious condition namely Chronic Lower Back Pain in which physicians must carry out a more involved diagnostic procedure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Due to numerous advances in medical image processing and AI, physicians are now able to optimize the time for their diagnosis and treatment. Around 60% to 80% of the population in the UK may have experienced back pain at any time in their life [46], and among chronic diseases worldwide, one-fourth of the population suffers back pain. Advances in AI have reduced the risk by having a fast diagnosis system, with early prevention of acute back pain becoming chronic back pain.…”
Section: Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to numerous advances in medical image processing and AI, physicians are now able to optimize the time for their diagnosis and treatment. Around 60% to 80% of the population in the UK may have experienced back pain at any time in their life [46], and among chronic diseases worldwide, one-fourth of the population suffers back pain. Advances in AI have reduced the risk by having a fast diagnosis system, with early prevention of acute back pain becoming chronic back pain.…”
Section: Back Painmentioning
confidence: 99%
“…Advances in AI have reduced the risk by having a fast diagnosis system, with early prevention of acute back pain becoming chronic back pain. Electromyography (EMG), heart-rate variability (HRV), pelvic incidence, pelvic tilt (Figure 1), lumbar lordosis angle, sacral slope, pelvic radius, degree spondylolisthesis, pelvic slope, direct tilt, thoracic slope, cervical tilt, sacrum angle and scoliosis slope, gait features, data from pressure sensors to assess sitting posture and erector spinae muscle activity are some explainable features for back pain diagnosis using AI [46][47][48][49][50][51].…”
Section: Back Painmentioning
confidence: 99%
“…We will also employ appropriate post-processing algorithms on the resulting segmentation to make it more suitable for medical image analysis purposes. The general plan is to use PALMSNet in our framework on computer-assisted detection of chronic lower back pain which was detailed in our previous publication [37].…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…The paper reported that 91% accuracy is achieved in detecting the herniation. More details about the related research are available in our previous publication [6].…”
Section: Related Researchmentioning
confidence: 99%
“…The focus of this paper is on labeling and localizing the disc area in the lumbar spine using the axial view MR images. In our previous work [6] we have developed a framework for detecting the disc herniation in the lumbar spine which require labeling the disc area to be able to detect the herniation. Currently diagnosing the lower back pain is done by a visual observation and analysis of the lumbar spine MR images and this process could take up much of a physician time and effort.…”
Section: Introductionmentioning
confidence: 99%